On the economics of power supply systems (2011)
In principle, this thesis was going to be oriented to study ?hedging strategies for a hydro power producer in the Colombian wholesale market? where stochastic programming would had been the central axis of the work. Even through, the dynamic regulatory environment within the Colombian power industry undermined the idea. Hence, and engaged in the seek for academic contributions committed with the national development. I have particularly emphasized upon the flaws and features of the Colombian wholesale electricity market. This thesis was thus oriented to give insights and solutions to particular economic issues concerning the local wholesale electricity market. This endeavor resulted in a document composed of diametrically opposite subjects which I strategically procured to frame within the theory concerning the economics and planning of integrated power supply systems. Aligning this thesis with the objective of producing contributions worth of being published by international scientific journals, the analysis and outcomes were summarized in the form of academic papers which if not already published, are currently in their corresponding process to be published. Theses papers are: 1.The strategic cost of hydroelectric resources 2.Setting up standard power options to hedge price-quantity risks in a competitive electricity market. The Colombian case. 3.Regulatory design and incentives for renewable energy. 4.A second thought about the Colombian wholesale electricity market. Despite the emphasis made upon the national framework, the way some of these problems were approached is not restrictive or specific. Some of them allow the further extension of the results obtained beyond national borders. In general, the activities undertaken yield ideas and results which, if properly addressed and implemented, could enhance the overall market performance of different competitive market settings and particularly, the Colombian wholesale electricity market